SOCIAL CRITISM IN THE NOVEL “SELAMAT TINGGAL” BY TERE LIYE - Rahmawati; Sri Suryana Dinar; Sulfiah (CASA CENDEKIA MEDIA, 2026)
This study aims to describe and analyze forms of social criticism in the novel Selamat Tinggal by Tere Liye. The research employs a qualitative approach using library research methods. The data consist of words, phrases, and sentences in the novel that reflect social criticism, particularly those related to social problems. Data were collected through intensive and analytical reading techniques and analyzed using an objective approach that focuses on the intrinsic structure of the text. The findings reveal that the novel contains five major forms of social criticism: poverty, crime, family disorganization, environmental issues, and population problems. Poverty is portrayed as a structural condition that restricts access to education and healthcare, while crime—especially intellectual property piracy—is depicted as a systemic issue resulting from weak legal protection and moral awareness. Family disorganization emerges as a consequence of economic pressure and insufficient social support, positioning families as vulnerable social institutions. In addition, environmental and population issues are presented as reflections of societal neglect and imbalance. This study concludes that Selamat Tinggal functions not only as a literary work but also as a medium of social reflection that critiques social inequality and injustice within contemporary Indonesian society. The social criticism presented in the novel encourages readers to develop social awareness and critical thinking toward existing social realities.